Oficina de foguete: aspectos interdisciplinares entre astronomia, astronáutica e física - Ferreira, Rodrigo Santa Cruz (2016)
This work discusses aspects of Astronautics and Astronomy in the Science and Physics classes of Elementary and Middle School in public and private schools in Feira de Santana. Astronomy is an interdisciplinary and necessary science in the curriculum of Brazilian schools. As such, we have a workshop where students build and launch rockets made of low-cost materials such as PET pickups and PVC pipes. The meaningful learning (Ausubel, 1976) was the theoretical reference of this study. Therefore,, we started the work by collecting information from the students through questionnaires to create a profile about their knowledge about astronomy and, after that, we propose activities where students are able to develop skills for understanding the physical phenomena that can be observed during the launch of a rocket, such as Oblique Motion and Newton's Laws. The workshop was very positive, arousing students' interest in participating in the Brazilian Astronomy and Astronautics Olympiads and obtaining better grades in the disciplines of Science and Physics. The students also realized the importance of astronomy in the development of humanity.